The effects of adaptation of appeals on the engagement of customers : A study on localised Instagram accounts of Coca-Cola in the USA, Finland, and the Philippines - Kukkonen, Akusti (My University, 2025)
Cultural differences have always played a significant role in international advertising and inter cultural communication. Cultural values stemming from these differences are often reflected in advertising appeals. Another important aspect of cultural differences is understanding intercul tural communication. It is essential in today’s world, where social media allows people to con nect instantly across national borders. Ineffective communication can lead to misunderstand ings and misinterpretations, which may result in lost customers, missed business opportunities, and damaged relationships. While the adaptation and standardisation of international market ing have been topics of extensive research, the findings have remained mixed and inconclusive. The presence and growth of social media platforms brings an ever-developing aspect to the mix. Instagram as a social media platform has not been researched extensively as it might have been overlooked due to even more popular platform Facebook. This study aims to add in the research literature regarding localised Instagram accounts and the effects on engagement of the custom ers the adaptation of the appeals of the content on those accounts has. Coca-Cola was chosen as the company to be used in this study because they are widely regarded as a company that adapts their marketing in different countries. This study has been further delimited to three countries: the USA, Finland and the Philippines. These countries were chosen due to the differences between their cultures, which enables the comparison between the ap peals that are used in the content of their localised Instagram accounts. This thesis has based its theoretical framework on the concepts of Hofstede´s cultural dimensions, Hall’s high- and low context communication and Pollay´s advertising appeals. The research method that is used in the empirical part of this study is quantitative research method with a deductive approach. The data for this study was collected by the author by coding a total of 60 Instagram posts (20 from each localised account) based on the appeals and engagement metrics found from the posts. The findings from statistical tests mostly supported the hypotheses regarding the appeals found from the posts of the localised Instagram accounts. This suggests that the advertising appeals and the ratings on different dimensions of the Hofstede model are in line with each other. How ever, the findings regarding the relationship between the appeals and engagement did not sup port the hypotheses that expected them to be positively related with each other. Possible rea sons for that might be the small sample size or the selected metric for measuring engagement.

Kulttuurierot ovat aina näytelleet suurta roolia kansainvälisessä markkinoinnissa sekä kulttuu rien välisessä kommunikaatiossa. Kulttuurilliset arvot, jotka johtavat juurensa näistä eroista nä kyvät markkinoinnin vetovoimatekijöissä. Toinen tärkeä elementti kulttuurieroissa on ymmärtää kulttuurien välistä kommunikaatiota. Se on erittäin tärkeää tämän päivän maailmassa, jossa so siaalinen media mahdollistaa ihmisten välittömän yhteyden muodostamisen toisiin, yli kansal listen rajojen. Kommunikoinnin toimimattomuus voi johtaa väärinymmärryksiin, joka voi vuo rostaan johtaa asiakkaiden menettämiseen, taloudellisten mahdollisuuksien menettämiseen sekä suhteiden heikkenemiseen tai jopa vaurioitumiseen. Vaikka kansainvälisen markkinoinnin sopeuttaminen ja standardisoiminen ovat laajasti tutkittuja aiheita, ovat niihin liittyvät tulokset olleet epäjohdonmukaisia ja sekalaisia. Sosiaalisen median kasvu tuo sekaan alati kehittyvän ele mentin. Instagramia ei ole tutkittu laajasti sosiaalisen median alustana, sillä se on vaikuttanut jääneen vielä suositumman alustan, Facebookin, varjoon. Tämän tutkimuksen tavoitteena on lisätä tieteellistä kirjallisuutta lokalisoiduista Instagram käyttäjistä ja kyseisten käyttäjien sisäl töjen vetovoimatekijöiden sopeuttamisen vaikutuksista asiakkaiden sitoutumiseen. Coca-Cola valittiin kohteeksi tähän tutkimukseen, sillä sitä on laajasti pidetty yrityksenä, joka sopeuttaa markkinointiaan eri maissa. Tämä tutkimus on suunnattu entisestään keskittymään kolmeen maahan: Yhdysvaltoihin, Suomeen ja Filippiineihin. Nämä maat valittiin niiden kulttuu rierojensa takia, mikä mahdollistaa niiden lokalisoitujen Instagram käyttäjien sisällöistä löyty vien vetovoimatekijöiden vertailemisen. Tämän tutkielman teoreettinen viitekehys perustuu Hofsteden kulttuurillisten ulottuvuuksien, Hallin korkean ja matalan kontekstin kommunikaa tion sekä Pollayn markkinoinnin vetovoimien teorioihin. Tämän tutkimuksen empiirisessä osi ossa käytetään kvantitatiivista tutkimusmenetelmää ja deduktiivista lähestymistapaa. Materi aali tähän tutkimukseen kerättiin koodaamalla yhteensä 60 Instagram julkaisua (20 jokaiselta käyttäjältä) niistä löytyviin vetovoimatekijöihin ja sitoutuneisuuden mittareihin perustuen. Tilastollisten testien tulokset suurimmalta osin tukivat hypoteeseja, jotka liittyivät lokalisoitujen Instagram käyttäjien sisällöistä löytyviin vetovoimatekijöihin. Tämä tarkoittaa, että vetovoima tekijät ja arvot tietyissä ulottuvuuksissa Hofsteden mallissa ovat linjassa keskenään. Tulokset vetovoimatekijöiden ja sitoutuneisuuden välillä eivät kuitenkaan tukeneet hypoteeseja, joiden mukaan niiden piti positiivisesti korreloida keskenään. Tämä saattaa johtua pienestä otoksen koosta tai sitoutuneisuuden mittaamiseen valitusta mittarista.
Keywords: social media; Instagram; cultural differences; appeals; advertising; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business